Optimisation of the superconducting properties of MgB2 prepared by the reaction of (MgB4 + Mg) and doping with silicon carbide - Tan, Kim Lee (2011)
In this work, MgB2 was synthesized by reaction of (MgB4 + Mg) and the superconducting properties of the samples were optimized by using the following routes: (i) variation of heat treatment, (ii) addition of excess Mg and (iii) addition of nano-SiC. The porosity of the samples was much reduced as compared to the sample prepared by reaction of (Mg + 2B). The samples were analyzed through XRD, SEM, physical density and superconducting properties measurements. Firstly, MgB4 powder was synthesized by direct reaction of Mg and B. Between HNO3 and HCl, the use of the former for immersing time of 5 minutes was found to be effective in removing MgO phase in the MgB4 sample sintered at 1050°C for 2 hours. Hence, the MgB4 powder with reduced amount of MgO was used as the precursor powders for the following reaction. The phase transformation from MgB4 to MgB2 was done by reacting MgB4 and Mg powders at the temperature range from 650°C to 950°C for 4 hours and 8 hours, respectively. The estimated weight fraction of MgB2 is the highest at 650°C and 750°C but it decreased above 850°C and upon increasing the sintering time, it changed slightly. With increasing sintering temperature, the transition temperature Tc decreased due to the lattice distortion of MgB2. The sample sintered at 750°C for 4 hours showed the highest magnetic Jc (4.23 × 104 A/cm2) at 5 K and 2 T which is consistent with the highest weight fraction of MgB2. Excess Mg powder was added into MgB4 to synthesize nominal MgxB2 (x = 1.2, 1.5 and 1.7) at 650°C and 750°C, respectively for 8 hours. The estimated weight fraction of MgB2 decreased upon increasing x level and it increased with the sintering temperature. However, the effect of excess magnesium and sintering temperature on Tc was not pronounced. With increasing x, Mg1.7B2 sample sintered at 650°C showed the highest Jc (7.59 × 104 A/cm2). Meanwhile at 750°C, Mg1.5B2 sample recorded the highest Jc (4.49 × 105 A/cm2), both at 5 K, 2 T. The Jc was enhanced by higher estimated weight fraction of MgB2 and the flux pinners (excess Mg). In order to study the influence of nano-particle on Jc, 2 wt. %, 5 wt. % and 10 wt. % of nano-SiC were added into the samples with nominal composition of Mg1.5B2 and sintered at 750°C for 4 hours. The estimated weight fraction of MgB2 decreased with SiC addition level. The a-axis decreased significantly indicating an increase in the C substitution at the B site upon increasing SiC addition level. Hence, Tc degraded with increasing SiC addition level due to the distortion of MgB2 lattice. The highest Jc of 1.52 × 104 A/cm2 achieved by MgB2 added with 2 wt. % of SiC were due to the C substitution that enhanced the scattering of the charge carrier and hence improved the field dependent Jc behavior. This work demonstrated that inexpensive way of using excess Mg as compared to SiC, could result in samples with higher value of Jc (5 K, < 5 T) but SiC showed weaker field dependence of Jc